Material Didáctico para Grado quinto “Caja de Herramientas para el Fortalecimiento de la Inteligencia Emocional en el área de Ciencias Sociales”. - Acuña Diaz, Nikol Alexandra (Universidad Antonio Nariño, 2022)
This degree work tackles the creation of a didactic material that strengthens and promotes the emotional intelligence in students who are in the stage of early adolescence. In a first moment, an identification of the need is made, in a second stage, the difficulty exploration is done, where the collection and creation of the state of the art were configured, with the theoretical framework and legal framework, these based on the emotional intelligence at the school and the emotional education.